Somatic Hypermutations Confer Rheumatoid Factor Activity in Hepatitis C Virus–Associated Mixed Cryoglobulinemia. Issue 9 (26th August 2013) - Charles, Edgar D.; Orloff, Michael I. M.; Nishiuchi, Eiko; Marukian, Svetlana; Rice, Charles M.; Dustin, Lynn B.
Abstract : Objective: Hepatitis C virus (HCV) is the most frequent cause of mixed cryoglobulinemia (MC), which is characterized by endothelial deposition of rheumatoid factor (RF)–containing immune complexes and end‐organ vasculitis. MC is a lymphoproliferative disorder in which B cells express RF‐like Ig, yet its precise antigenic stimulus is unknown. We have proposed that IgG–HCV immune complexes stimulate B cell expansion and somatic hypermutation (SHM)–induced affinity maturation in part via engagement of an RF‐like B cell receptor. This study was undertaken to test the hypothesis that SHM augments RF activity. Methods: RFs cloned from single B cells from 4 patients with HCV‐associated MC (HCV‐MC) were expressed as IgM, IgG, or IgG Fab. Selected Ig were reverted to germline. RF activity of somatically mutated Ig and germline‐reverted Ig was determined by enzyme‐linked immunosorbent assay. Results: Ig with SHM had RF activity, with the preference for binding being highest for IgG1, followed by IgG2 and IgG4, and lowest for IgG3, where there was no detectable binding. In contrast, reverted germline IgG exhibited markedly diminished RF activity. Competition with 1 μg/ml of protein A abrogated RF activity, suggesting specificity for IgG Fc. Swapping of mutated heavy‐chain pairs and light‐chain pairs also abrogated RF activity, suggesting that context‐specific pairing of appropriate IgH and Igκ, in addition to SHM, is necessary for RF activity. Conclusion: SHM significantly contributes to RF activity in HCV‐MC patients, suggesting that autoreactivity in these patients arises through antigen‐dependent SHM, as opposed to nondeletion of autoreactive germline Ig.